Truth, lies and advertising : the art of account planning - Steel, Jon (Chichester [etc.] John Wiley & Sons, 1998)
"Account planning exists for the sole purpose of creating advertising that truly connects with consumers. While many in the industry are still dissecting consumer behavior, extrapolating demographic trends, developing complex behavioral models, and measuring Pavlovian salivary responses, Steel advocates an approach to consumer research that is based on simplicity, common sense, and creativity--an approach that gains access to consumers' hearts and minds, develops ongoing relationships with them, and, most important, embraces them as partners in the process of developing and advertising.<U+000d><U+000a><U+000d><U+000a>A witty, erudite raconteur and teacher, Steel describes how successful account planners work in partnership with clients, consumer, and agency creatives. He criticizes research practices that, far from creating relationships, drive a wedge between agencies and the people they aim to persuade; he suggests new ways of approaching research to cut through the BS and get people to show their true selves; and he shows how the right research, when translated into a motivating and inspiring brief, can be the catalyst for great creative ideas. He draws upon his own experiences and those of colleagues in the United States and abroad to illustrate those points, and includes examples of some of the most successful campaigns in recent years, including Polaroid, Norwegian Cruise Line, Porsche, Isuzu, "got milk?" and others.<U+000d><U+000a><U+000d><U+000a>The message of this book is that well-thought-out account planning results in better, more effective marketing and advertising for both agencies and clients. And also makes an evening in front of the television easier to bear for the population at large."
Keywords: Publicidad -- EEUU; Agencias publicitarias -- EEUU